Season rather than habitat affects lynx survival and risk of mortality in the human‐dominated landscape of southern Sweden. Issue 1 (15th December 2021) - Andrén, Henrik; Aronsson, Malin; López‐Bao, José V.; Samelius, Gustaf; Chapron, Guillaume; Rauset, Geir Rune; Hemmingmoore, Heather; Persson, Jens
Abstract : Landscapes are mosaics of habitat associated with different risks and resources, including human activities, which can affect individual survival in wildlife. Different relationships between habitat characteristics and human‐caused and natural mortality can result in attractive sinks. We used individual‐based data from 97 Eurasian lynx Lynx lynx monitored for 160 exposure‐years to link adult survival and the risk of mortality to home range habitat characteristics in the human‐dominated landscape of southern Sweden. Human‐caused mortality (i.e. legal hunting, poaching and vehicle accidents) dominated mortality causes (24 out of 37 deaths). We did not detect any strong effects of habitat characterises explaining the variation in mortality risk in lynx. Although the density of roe deer affects several aspects of lynx ecology, we could not detect any effects of roe deer density on lynx survival, probably because roe deer density was sufficiently high in our study area. Instead, seasonal variation was the main factor influencing mortality in lynx. Mortality was highest during the hunting season for lynx (16 February–31 March), as well as during autumn and winter, probably because lynx poaching occurs opportunistically during the hunting season for moose and roe deer. We did not find any indication that human activity created attractive sinks for lynx, since there were no contrasting patterns between human‐caused and natural mortality in terms of habitat characteristics. One explanation for the limited influence of the home range characteristics may be that lynx in our study died from multiple causes. Therefore, it is less likely that one or a few habitat characteristics could explain the risk of mortality at the home range scale. There is strong evidence that lynx can coexist with humans in multi‐use and human‐dominated landscapes, even without large protected areas, if the management regimes are favourable.